Genome-wide analysis of cucumber (Cucumis sativus L.) Lines to identify zucchini yellow mosaic virus resistance loci - Coşkun, Ömer Faruk; Gökbulut, Tarik; Fidan, Hakan; Firat, Ahmet Fikret; Pina, Hasan; Gülşen, Osman (Bangladesh Journal of Botany, 2024)
Zucchini yellow mosaic virus (ZYMV) is one of the most important pathogens that cause yield losses in cucumber. The objectives of this study were to investigate the structure of genetic resistance to ZYMV in cucumber for marker-assisted selection (MAS). Forty-eight resistant and 48 susceptible lines were selected from a germplasm collection of 600 cucumber lines. Bulk DNAs of resistant and susceptible lines were screened to find candidate marker(s) using ISSR, RAPD, and a cleaved amplified polymorphism (CAP) primer, which targeted over 5000 cucumber loci. A total of 54 candidate marker loci were identified. In association analyses using TASSEL software, associated markers were detected. The results explained 78% of the total ZYMV variation. The remaining 22% of the variation was possibly due to the presence of additional genes and environmental effects that caused lower repeatability. The markers developed in this study may allow successful discrimination of resistant and susceptible cucumbers for markers assisted selection in breeding programs. Bangladesh J. Bot. 53(4): 895-902, 2024 (December)